2022
DOI: 10.1007/s00382-022-06319-9
|View full text |Cite
|
Sign up to set email alerts
|

Representation of sea ice regimes in the Western Ross Sea, Antarctica, based on satellite imagery and AMPS wind data

Abstract: Sea ice drift data at high spatial resolution and surface wind model output are used to explore atmosphere-sea ice interactions in the Western Ross Sea including the three main polynyas areas; McMurdo Sound polynya (MSP), Terra Nova Bay polynya (TNBP), and the Ross Sea polynya (RSP). This study quantifies the relationship between the winds and sea ice drift and observes the average and annual anomalies across the region. Sea ice drift velocities are based on high-resolution (150 m) Advanced Synthetic Aperture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The PAR is a divergent tectonic plate boundary located on the seafloor extending from approximately 56°S to Antarctica that separates the Pacific and Antarctic plates (Figure 2) and represents an important hot spot of EKE (Falco & Zambianchi, 2011). The observed sea‐ice protrusion has been previously linked to atmospheric factors, such as the Amundsen Sea Low (e.g., Fogt and Scambos, 2013, 2014; Fogt and Stammerjohn, 2015; Scambos and Stammerjohn, 2018, 2019; Stammerjohn, 2016; Stammerjohn and Scambos, 2017; Turner et al., 2009, 2016), the Southern Annular Mode (e.g., Marshall, 2003; Son et al., 2010) and the katabatic wind regimes (e.g., Farooq et al., 2023) that can explain part of its seasonal and interannual variability. Conversely, few studies have analyzed if/how local bathymetry exerts a control on this protrusion and what allows its recurrent formation, besides the seasonal and interannual variability driven by oceanic and atmospheric forcing (Nghiem et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The PAR is a divergent tectonic plate boundary located on the seafloor extending from approximately 56°S to Antarctica that separates the Pacific and Antarctic plates (Figure 2) and represents an important hot spot of EKE (Falco & Zambianchi, 2011). The observed sea‐ice protrusion has been previously linked to atmospheric factors, such as the Amundsen Sea Low (e.g., Fogt and Scambos, 2013, 2014; Fogt and Stammerjohn, 2015; Scambos and Stammerjohn, 2018, 2019; Stammerjohn, 2016; Stammerjohn and Scambos, 2017; Turner et al., 2009, 2016), the Southern Annular Mode (e.g., Marshall, 2003; Son et al., 2010) and the katabatic wind regimes (e.g., Farooq et al., 2023) that can explain part of its seasonal and interannual variability. Conversely, few studies have analyzed if/how local bathymetry exerts a control on this protrusion and what allows its recurrent formation, besides the seasonal and interannual variability driven by oceanic and atmospheric forcing (Nghiem et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The definition utilises an unsupervised machine learning algorithm (k-means clustering) to classify the data into distinct sea ice regions. Unsupervised methods have been used to separate different sea ice types (e.g., Massom et al, 1999, used satellite data), and the k-means algorithm has been shown to be appropriate for climate science applications (Wilks, 2011) including sea ice data retrieved from satellites (Farooq et al, 2023) and models (LIM3 Moreno-Chamarro et al, 2020). We specify the number of clusters to k-means based on a wave heuristic, such that the outer cluster is the regularly wave-affected sea ice region, i.e., the description of the MIZ, without explicitly including waves properties in the clustered dataset.…”
Section: Introductionmentioning
confidence: 99%